2006
DOI: 10.1210/en.2005-0958
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-4 Inhibits Corticotroph Tumor Cells: Involvement in the Retinoic Acid Inhibitory Action

Abstract: The molecular mechanisms governing the pathogenesis of ACTH-secreting pituitary adenomas are still obscure. Furthermore, the pharmacological treatment of these tumors is limited. In this study, we report that bone morphogenetic protein-4 (BMP-4) is expressed in the corticotrophs of human normal adenohypophysis and its expression is reduced in corticotrophinomas obtained from Cushing's patients compared with the normal pituitary. BMP-4 treatment of AtT-20 mouse corticotrophinoma cells has an inhibitory effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 52 publications
8
79
0
Order By: Relevance
“…Expression of several other regulators of BMP-4 signaling is also induced by BMP-4, raising the possibility that blockade of relevant signaling inhibitors might enhance the efficacy of BMP-4 treatment. Previous in vivo studies have described antitumorigenic effects of BMP-4 for (40,(45)(46)(47)-as well as protumorigenic effects for some-but thus far only one other study, using a model of glioblastoma multiforme, has demonstrated an antitumor effect of therapeutically administered recombinant BMP-4 (48). Although the authors identified a prodifferentiation effect on tumor stem cells, we noted that VEGF-D is highly expressed in glioblastoma multiforme (49).…”
Section: Discussionmentioning
confidence: 59%
“…Expression of several other regulators of BMP-4 signaling is also induced by BMP-4, raising the possibility that blockade of relevant signaling inhibitors might enhance the efficacy of BMP-4 treatment. Previous in vivo studies have described antitumorigenic effects of BMP-4 for (40,(45)(46)(47)-as well as protumorigenic effects for some-but thus far only one other study, using a model of glioblastoma multiforme, has demonstrated an antitumor effect of therapeutically administered recombinant BMP-4 (48). Although the authors identified a prodifferentiation effect on tumor stem cells, we noted that VEGF-D is highly expressed in glioblastoma multiforme (49).…”
Section: Discussionmentioning
confidence: 59%
“…A binding protein for BMPs, noggin expression is conversely downregulated in the prolactinoma from the D2R-null mouse (Paez-Pereda et al 2003), suggesting that BMP-4 promotes cell proliferation in lactotropes in conjunction with Smad-estrogen receptor interaction under the influence of its binding protein. BMP-4 also inhibits adrenocorticotropin secretion and cell proliferation of corticotropinoma cells (Giacomini et al 2006). This BMP-4 action seems to be involved in the anti-proliferative effect induced by retinoic acid on corticotropinomas.…”
Section: Discussionmentioning
confidence: 91%
“…This BMP-4 action seems to be involved in the anti-proliferative effect induced by retinoic acid on corticotropinomas. Thus, BMP-4 promotes pituitary prolactinoma through Smad-estrogen receptor crosstalk (Paez-Pereda et al 2003) while BMP-4 inhibits corticotrope pathogenesis of Cushing's disease (Giacomini et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinoic acid induces both BMP-4 transcription and expression and its antiproliferative action is blocked in Smad-4 dominant negative and noggin transfected Att-20 cells that do not respond to BMP-4. Therefore, BMP-4 is induced by and mediates some of the retinoic acid effects [62].…”
Section: Bmp-4 Involvement In the Retinoic Acid Inhibitory Actionmentioning
confidence: 99%